Traumatic laser in situ keratomileusis flap dislocation with epithelial ingrowth, Propionibacterium acnes infection, and diffuse lamellar keratitis: A case report. Issue 10 (March 2020) - Chang, Yung-Ching; Lee, Yuan-Chieh
Abstract: Rationale: Traumatic flap dislocation might occur anytime after laser in situ keratomileusis (LASIK), but it is rarely concomitantly complicated with epithelial ingrowth, infectious keratitis, and diffuse lamellar keratitis altogether. Here we report a case of traumatic LASIK flap inversion with epithelial ingrowth, Propionibacterium acnes infection, and diffuse lamellar keratitis. Patient concerns: A 42-year-old man receiving bilateral LASIK surgery 10 years ago complained of right eye pain for 6 days after twig injury. Temporal flap inversion with epithelial ingrowth and dense infiltration at the interface were noted. Diagnoses: Traumatic LASIK flap inversion with epithelial ingrowth, Propionibacterium acnes infection and diffuse lamellar keratitis. Interventions: Removal of corneal epithelium around the flap inversion site, flap lifting, scraping of epithelial ingrowth, removal of the dense infiltrate, alcohol soaking, interface irrigation with antibiotics, and flap reposition were performed. Diffuse lamellar keratitis was noted postoperatively. Culture of the infiltrate revealed P acnes . The infiltrate subsided and the cornea cleared up under topical antibiotics and steroid. Outcomes: The visual acuity returned to 20/20. No recurrent epithelial ingrowth or infiltrate was noted during the follow-up. Lessons: This is the first report of Propionibacterium acnes keratitis after traumatic flap inversion. Although epithelial ingrowth, infectious keratitis, and diffuse lamellar keratitis all developed after the flap inversion, early recognition and proper intervention lead to a good result without sequels.